2005
DOI: 10.1016/j.ijhcs.2005.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between organizational and user perspectives of security in the clinical domain

Abstract: Abstract:An understanding of 'communities of practice' can help to make sense of existing security and privacy issues within organisations; the same understanding can be used proactively to help bridge the gap between organisational and end-user perspectives on these matters. Findings from two studies within the health domain reveal contrasting perspectives on the 'enemy within' approach to organisational security. Ethnographic evaluations involving in-depth interviews, focus groups and observations with 93 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The interviewed experts explained the opinions differed as a result of varied levels of perceived ownership of tasks in terms of their capacity to complete assigned tasks. This explanation supported findings from Adams and Blandford (2005) and Posey et al (2014) that there would be discrepancies in the security experts and end-users' ownership of the security compliance activities, as well as their perceptions of the severity and likelihood of security threats.…”
Section: Factor 1: Security Risk Evaluationsupporting
confidence: 72%
See 2 more Smart Citations
“…The interviewed experts explained the opinions differed as a result of varied levels of perceived ownership of tasks in terms of their capacity to complete assigned tasks. This explanation supported findings from Adams and Blandford (2005) and Posey et al (2014) that there would be discrepancies in the security experts and end-users' ownership of the security compliance activities, as well as their perceptions of the severity and likelihood of security threats.…”
Section: Factor 1: Security Risk Evaluationsupporting
confidence: 72%
“…Several studies have explored such perspectives. For instance, different perceptions of ownership over security issues amongst staff and managers were found to result in end-users' rejection of security controls by forcefully breaking into the computer room (Adams and Blandford 2005). Disagreements on the effectiveness of security controls and preferences between management and technical staff were also noted in Mouratidis et al (2008) where the management staff had doubts about the organisation's network security system in spite of the security team's confidence in the system's effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors propose a semiquantitative risk evaluation framework, suggesting to act upon each identified risk if the standard "C < LD" equation is satisfied. 10 To evaluate the components of this formula, a set of risk management questions are used, listed in Table 3.9.…”
Section: Risk Analysismentioning
confidence: 99%
“…Developing the "human" side of the policies should be a priority for the MIS and CSCW communities, as shown by the work by Adams and Blandford. Adams and Blandford discuss the effects of the introduction of access control systems to patient data within a health care settings [10]. They studied two hospitals through in-depth interviews, focus groups, and observations, and found that in one hospital, a user-centered approach resulted in a collaborative system that was accepted and used by the organization, but still clashed with existing working practices.…”
Section: Better Organizational Practicesmentioning
confidence: 99%